2016
DOI: 10.1007/s00114-016-1404-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen isotope fractionation between bird eggshell calcite and body water: application to fossil eggs from Lanzarote (Canary Islands)

Abstract: Oxygen and carbon isotope compositions of fossil bird eggshell calcite (δ 18 Ocalc and δ 13 Ccalc) are regularly used to reconstruct paleoenvironmental conditions. However, the interpretation of δ 18 Ocalc values of fossil eggshells has been limited to qualitative variations in local climatic conditions as oxygen isotope fractionations between calcite, body fluids, and drinking water have not been determined yet. For this purpose, eggshell, albumen water, and drinking water of extant birds have been analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Pooling this fractionation factor with those established for five extant birds (the common quail Coturnix coturnix , the chicken Gallus gallus , the Egyptian goose Alopochen aegyptiaca , the mallard duck Anas platyrhynchos and the ostrich Strutio camelus ; Table ; Lazzerini et al . ), no relationship was observed between α c–ew and body temperature (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pooling this fractionation factor with those established for five extant birds (the common quail Coturnix coturnix , the chicken Gallus gallus , the Egyptian goose Alopochen aegyptiaca , the mallard duck Anas platyrhynchos and the ostrich Strutio camelus ; Table ; Lazzerini et al . ), no relationship was observed between α c–ew and body temperature (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
“…According to Lazzerini et al . (), terrestrial birds display a drinking water‐body water 18 O‐enrichment of about +4‰ (at least in ostrich and chicken). Based on the egg water δ 18 O ew value of −5.7‰ calculated for NHGM10876, a δ 18 O w value of local surface waters of about −9.7‰ can be estimated.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Later, Johnson et al [ 18 ] would find that the linear relationship between δ 18 O of eggshell carbonate and water source did not hold true in wild ostriches, indicating that this relationship might not be a reasonable assumption to make in open ecosystems where body water is obtained from a variety of sources such as plants. Lazzerini et al [ 40 ] calculated the oxygen isotope fractionation between ingested water and eggshell calcite and found it is in fact correlated in numerous bird species and could be used for palaeoenvironmental reconstruction, but the amount of enrichment was different for terrestrial and semi-aquatic birds. Even if absolute oxygen isotope fractionation factors are not known, Miller & Fogel [ 41 ] illustrated with modern emu eggshell from around Australia that eggshell δ 18 O can be a strong proxy for both modern and palaeo-aridity, emphasizing the importance of δ 18 O in the inorganic portion of eggshells for reconstructing palaeoenvironments.…”
Section: Ecological and Environmental Indicatorsmentioning
confidence: 99%
“…Air-breathing vertebrates have a body water 18 O-enriched relative to environmental water, the magnitude of which depends on the amount of body water loss through exhaled water vapour and transcutaneous evaporation. Direct measurements have shown that terrestrial mammals and birds have body water from about 4 to 7‰ 18 O-enriched relative to their drinking water [33][34][35], whereas the body waters of semi-aquatic to aquatic crocodylians, turtles and birds are about 2 to 3‰ 18 Oenriched relative to their drinking water [33,36,37].…”
Section: Introductionmentioning
confidence: 99%